IMPROVING FINE MOTOR ABILITIES OF EARLY CHILDHOOD THROUGH DRAWING AND COLORING ACTIVITIES BASED ON PARTICIPATORY ACTION RESEARCH AT INTEGRATED PAUD KEMALA BHAYANGKARI 14 PANYABUNGAN - Riani Agustina; Najwa Lubis; Kholidah Nur; Selvina Armiah; Nurainun Nurainun; Putri Salsabila; Rizky Aulia; Nova Elliza (LPPM Univ. Ibn Khaldun Bogor, 2026)
This study aims to improve the fine motor skills of early childhood through the implementation of drawing and coloring activities in the Integrated PAUD Kemala Bhayangkari 14 Panyabungan. The study used a Participatory Action Research (PAR) approach with two cycles including the planning, implementation, observation, and reflection stages. The activity involved 133 students divided into groups of Kindergarten A and Kindergarten B. The research instrument used an observation sheet with a rating scale of 1-4, namely Very Well Developed (BSB), Developed According to Expectations (BSH), Starting to Develop (MB), and Not Yet Developed (BB) and analyzed using percentages to see improvements between cycles. The results showed an increase in the percentage of the BSB category from 27% in cycle I to 46% in cycle II. These findings indicate that drawing and coloring activities designed in a structured and reflective manner are effective in stimulating the fine motor development of early childhood.